Caterpillars in the Field and Garden : a Field Guide to the Butterfly Caterpillars of North America. - Allen, Thomas J., 1940- (Oxford University Press, 2006)
With an emphasis on conservation and more than nine hundred full-color photographs, a comprehensive field guide furnishes all the information necessary for finding and identifying caterpillars, with information on key physical characteristics, habitats, and host plants and tips on butterfly gardening.